Nanoporous Carbon from Oil Palm Leaves via Hydrothermal Carbonization-Combined KOH Activation for Paraquat Removal - Sirayu Chanpee; Napat Kaewtrakulchai; Narathon Khemasiri; Apiluck Eiad-ua; Pornsawan Assawasaengrat (My University, 2022)
In this study, nano-porous carbon was completely obtained from oil palm leaves (OPL) by hydrothermal pretreatment with chemical activation, using potassium hydroxide (KOH) as an activating agent. Potassium hydroxide was varied, with different ratios of 1:0.25, 1:1, and 1:4 (C: KOH; w/w) during activation. The physical morphology of nano-porous carbon has a spongy, sponge-like structure indicating an increase in specific surface area and porosity with the increasing amount of KOH activating agent. The highest specific surface area of OPL nano-porous carbon is approximately 1685 m2·g-1, with a total pore volume of 0.907 cm3·g-1. Moreover, the OPL nano-porous carbon significantly showed a mesoporous structure designed specifically to remove water pollutants. The adsorptive behavior of OPL nano-porous carbon was quantified by using paraquat as the target pollutant. The equilibrium analyzes were explained by the Langmuir model isotherm and pseudo-second-order kinetics. The maximum efficiency of paraquat removal in wastewater was 79%, at a paraquat concentration of 400 mg·L-1, for 10 min in the adsorption experiment. The results of this work demonstrated the practical application of nano-porous carbon derived from oil palm leaves as an alternative adsorbent for removing paraquat and other organic matter in wastewater.
Keywords: Potassium hydroxide; Specific surface area; Carbon fibers; Nanoporous; Hydrothermal Carbonization; Paraquat toxicity studies and treatments